Frasier syndrome: A rare syndrome with WT-1 gene mutation - Sundaram, Vindhiya Kadambavana; Subramanian, Sundari; Chinumuthu, Lakshmi Charan; Dharmanathan, Aishwarya (International Journal of Contemporary Pediatrics, 2017)
Frasier syndrome is a rare disorder of sex development. It is caused by mutation in Wilms’ tumor suppressor gene (WT-1) located in 11p23. This gene encodes a transcription factor involved in the development of kidney and gonads. The syndrome is characterized by female external genitalia in 46, XY patients, streak gonads with a higher risk of gonadal tumors, mainly gonadoblastoma. Nephropathy consists of nephrotic syndrome (NS) mainly due to focal segmental glomerular sclerosis (FSGS). NS presents early in childhood and responds poorly to steroid and immunosuppressive agents. Progression to End Stage Renal Disease (ESRD) usually occurs by second or third decade of life. We present a 6 years old female child with insignificant past medical history diagnosed as steroid resistant nephrotic syndrome. Renal biopsy showed FSGS. CT Abdomen showed streak gonads with rudimentary uterus. Further genotype showed WT-1 mutation with Karyotype of 46XY. Elective bilateral gonadectomy was done and histopathology showed bilateral dysgerminoma. After a year, her disease progressed to ESRD and she succumbed to the illness.